An examination of the methods of mixing peroxides into polythene to form polymer networks - Stuart, J. M. (College of Aeronautics, 1963)
In the production of peroxide cross-linked polyethylenes it is customary to introduce the organic peroxide by the hot milling process. Inevitably some peroxide is lost by volatilization and the process is, therefore, difficult to standardize. In this paper, the efficiencies of the processes in which the peroxide is introduced by wet and dry powder mixing are compared with the efficiency of the normal method of mill mixing. It is shown that in both the wet and dry processes the loss of peroxide is avoided, but that the dry mixed material shows inhomogeneities in the cross-linked state.